Homicide, race, and justice in the American West, 1880-1920 - McKanna, Clare V., Jr., 1935-2012 (Book collections on Project MUSE., 1997)
As a beginning point for actually measuring lethal violence and assessing the administration of justice, here at last is a detailed and well-documented study of homicide in the American West. Comparing data from representative areas - Douglas County, Nebraska; Las Animas County, Colorado; and Gila County, Arizona - this book reveals a level of violence far greater than many historians have believed, even surpassing eastern cities like New York and Boston.